2018
DOI: 10.14740/wjon1163
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carcinoembryonic Antigen Level Predicts Cancer-Specific Outcomes of Resected Non-Small Cell Lung Cancer With Interstitial Pneumonia

Abstract: BackgroundIt has been well accepted that the prognosis of non-small cell lung cancer (NSCLC) patients with interstitial pneumonia (IP) is significantly poor. However, there are only a few studies that indicated the prognostic factors, especially tumor markers, among NSCLC patients with IP.MethodsForty-one NSCLC patients with IP who underwent surgery at our institution were included. Patients died of other diseases including postoperative acute exacerbation (AE) of IP were excluded. Univariate and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The level of protein biomarkers' specificity mainly depends on the cutoff value. In the current study, we established the cutoff values for CEA, CYFRA21-1, and SCC at 7.3 ng/mL, 4 ng/mL, and 2.5 ng/mL, respectively, based on previous reports 3 , 21 - 24 . These values are all above the clinical standard cutoff level (5 ng/mL, 3.3 ng/mL, and 1.5 ng/mL, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The level of protein biomarkers' specificity mainly depends on the cutoff value. In the current study, we established the cutoff values for CEA, CYFRA21-1, and SCC at 7.3 ng/mL, 4 ng/mL, and 2.5 ng/mL, respectively, based on previous reports 3 , 21 - 24 . These values are all above the clinical standard cutoff level (5 ng/mL, 3.3 ng/mL, and 1.5 ng/mL, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 , 21 ] PII and SIRI, which are derived by simple calculation from LY, NE, MO, CRP, and ALB, can reflect both the immune and systemic nutritional status of patients. [ 6 , 10 ] To the best of our knowledge, there are no domestic or international relevant studies on the auxiliary diagnostic value of PII and SIRI for pulmonary TB. The results of this study showed that LY, ALB, and PA were significantly lower in the case group as compared to the control group ( P < .05); while NE, MO, CRP, FIB, ESR, NLR, PII, and SIRI were significantly higher in the case group ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…[6–9] PII and SIRI are calculated according to the laboratory indicators of patients during hospitalization, which has the added advantages of simplicity and convenience. [6,10] Pathological changes in pulmonary TB mainly include inflammatory exudation, hyperplasia, and caseous necrosis. [11] To the best of our knowledge, no study has utilized the efficacy of PII and SIRI in the diagnosis of bacteria-negative pulmonary TB.…”
Section: Introductionmentioning
confidence: 99%